RANCANG BANGUN ALAT PENCAMPUR DESINFEKTAN OTOMATIS (STUDI KASUS PENCEGAHAN PANDEMI COVID-19) - Hari Bangun; Agus Ulinuha (Emitor: Jurnal Teknik Elektro, 2022)
The Coronavirus pandemic or Covid-19 caused by Corona Virus which spread widely in 2020 is very dangerous because it threatens the safety of humanity by means of very fast and easy transmission. One of the most popular prevention efforts is the use of disinfectants to eradicate the corona virus. This study examines an automatic disinfectant mixer which uses a flow meter sensor to measure the flowing solution and the volume of the solution. In addition, this tool also uses a solenoid valve as a cover and automatic valve opening that regulates the running of water. This automatic disinfectant mixer is controlled by the Atmega328P microcontroller at Arduino nano board. In this study the capacity is limited from 1 liter to 5 liters of disinfectant with the composition per liter of disinfectant consisting of 905 mL of water and 95 mL of sodium hypochlorite, while the DC motor will stir for 2 seconds. The results of testing this tool, the flow meter can read the flow and the volume of liquid, but there is an error in the calibration of the flow meter sensor of 0.21 to 1.8%, while in testing the disinfectant volume capacity, this tool can mix disinfectants from water and sodium hypochlorite to a maximum volume capacity of 5 liters, but there is a difference of up to 100-170 mL, between the specified disinfectant capacity and the disinfectant volume contained in the measuring cup.